Análisis del uso de Polímero Reforzado con fibras (FRP) como material estructural para el diseño de puentes peatonales - Bonilla Silva, Ronny Gabriel (2021)
This research work is based on the analysis of an alternative material called Fiber Reinforced Polymer or FRP to reinforce concrete structures, which brings some advantages such as high tensile strength, lightness, ease of assembly and long useful life compared to traditional materials, the aim is to broaden the knowledge about the design of structural elements reinforced with this material. The documents that mention this kind of structures reinforcement of with this material, show three different types of composite polymeric fibers called: glass fiber (GFRP), aramid fiber (AFRP) and carbon fiber (CFRP), each one have different mechanical properties and applications, carbon fiber seem to be the one that has the greatest contribution in terms of structural efficiency due to its high modulus and resistance in relation to its weight, allowing the elaboration of small structures such is the case of pedestrian bridges. For the design of the main structural elements subjected to flexural forces, it is necessary to know the different mechanical properties such as: density, Poisson's ratio, elasticity modulus and tensile strength, these parameters are used for the design, following codes such as ACI. 440-2R and AASHTO “FRP Pedestrian Bridge Specification” for the analysis of acting loads on pedestrian bridges. Finally, references of pedestrian bridges conceived in this material were analyzed, all the design parameters already studied were evaluated, such as: type of material used, live loads, sections, and structural forms